Letter from the Wilderness - Mullen, Mark (Eludamos: Journal for Computer Game Culture, 2009)
In a November 2006 Gamasutra article titled “We’re not listening: An Open Letter to Academic Game Researchers” John Hopson argues that much of the research into games by academics is not presented in a way likely to appeal to game developers and is largely irrelevant to their concerns. Hopson’s argument implicates humanities and many social science researchers producing speculative and descriptive research rather than more hard-edged technical and statistical research that can have an immediate impact on a game’s bottom line. While conceding Hopson’s point about the ineffectiveness of many academic communication norms, I argue that Hopson’s article is indicative not of problems with academic research into games as much as the position of game development toward the utility of academic research in general. After analyzing the assumptions underlying Hopson’s argument, I offer a schema that articulates several key types of research into games carried out by scholars with a primary background in the humanities and the contribution of each research approach to the game development process.